Seismic performance of a pile-supported wharf: Three-dimensional finite element simulation - Su, Lei; Lu, Jinchi; Elgamal, Ahmed; Arulmoli, Arul K. (Soil dynamics and earthquake engineering (1984), 2017)
Considerable three-dimensional (3D) effects are involved in the seismic performance of pile-supported wharves. Such effects include the pile-to-pile interaction mechanisms as dictated by the behavior of the surrounding soil. This interaction might be further affected by potential ground slope settlement/heave, and the constraint of pile connectivity along the relatively rigid wharf deck. In order to capture a number of these salient response characteristics, a 3D finite element (FE) study is conducted herein. The prototype system motivating this study is presented, along with the corresponding numerical details. A realistic multi-layer soil profile is considered, with interbedded relatively soft/stiff strata. Effect of the resulting seismically-induced ground deformation on the pile-supported wharf system is explored. Specific attention is drawn to the noteworthy potential changes in axial force due to variation in pile embedment depth, and the ground slope deformation. The analysis technique as well as the derived insights are of significance to general pile-wharf-ground system configurations. •A seismic 3D finite element analysis framework for pile supported wharf structures is developed.•It is shown that response of the piles is substantially dictated by the resulting soil deformation mechanisms.•The resulting pile axial forces, shear forces, and bending moments are thoroughly analyzed.•Motivated by the associated vertical slope movement and deformation, substantial additional pile axial forces may occur.